COVID-19 Pandemic and Ghana’s Economy: A Deep Dive into Economic Indicators - Peprah, Williams Kwasi; Anowuo, Isaac; Owusu-Yeboah, Ebenezer; Ameyaw, Daniel Adofo Kwakye; Sabas, Lucile (International Journal of Economics and Financial Issues, 2024)
The study presents an in-depth analysis of the COVID-19 pandemic’s effect on Ghana’s gross domestic product (GDP), balance of payments and international investment position (BPM6), and inflation (INFL). Employing a pre-and post-COVID-19 comparison (2017-2022) through repeated measures ANOVA and tests of between-subject effects, it investigates whether the government’s economic performance was significantly impacted. Key findings show a notable decrease in GDP and BPM6, alongside a major increase in inflation rates post-pandemic. The study concludes that the COVID-19 pandemic had a statistically significant impact on Ghana’s economic performance in terms of GDP and BPM6, but not inflation. Recommendations include implementing economic stabilization policies, managing the balance of payments, controlling inflation, and focusing on sustainable growth. These insights are crucial for policymakers and stakeholders in navigating Ghana’s post-COVID-19 economic situation.